Evaluation of a structured patient education protocol to achieve symptomatic pain relief and reduction in anxiety in patients with mastalgia: a randomized controlled trial - Pavithra Balakrishna; Meenakshi Yeola; Srikanth Marthandam; Ippili Tulasi; Punith Kumar (International Surgery Journal, 2026)
Background: Mastalgia is the most common presentation to Breast Clinics, reassurance forms the first line of management. No studies have explored structured patient education in mastalgia till date. Methods: Patients with mastalgia for more than 1 month were randomized to structured patient education and reassurance group. The structured patient education format was designed by the principal investigator and validated by 3 subject experts. Both the groups were assessed with visual analog scale (VAS) for pain, 12-item short form health survey (SF-12) for quality of life and generalized anxiety disorder-7 scale (GAD-7) for anxiety at baseline, 4 and 12 weeks after intervention. The assessor was blinded. Results: A total of 64 patients were randomized equally into two groups. Both groups showed improvement in pain and anxiety scores over time. A statistically significant improvement in the SF-12 physical component summary (PCS) was observed in the structured education group at 12 weeks (p=0.032). Improvements in mental component summary (MCS) and GAD-7 anxiety scores were observed in both groups, but without statistically significant difference. Analgesic use decreased in both groups, with a trend toward greater reduction in the structured education group. Conclusions: Structured patient education improves the physical component of quality of life in women presenting with mastalgia and may contribute to better overall symptom control compared to routine reassurance alone. While both interventions reduce pain and anxiety, structured education provides a standardized and potentially more effective approach to patient counselling.